PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP RETURN SAHAM DAN DAMPAKNYA TERHADAP REPUTASI PERUSAHAAN (STUDI KASUS PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2015-2020) - Jasmadeti Jasmadeti; Amrulloh Amrulloh (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the effect of Capital Structure and profitability (NPM) on stock returns and company reputation in property and real estate companies listed on the Indonesia Stock Exchange in the 2015-2020 period. This study consists of two independent variables regarding capital structure and profitability, and the dependent variable 1 regarding stock returns and the dependent variable 2, namely the company's reputation. The data used is secondary data which can be accessed through www.idx.co.id. Hypothesis testing in this study uses panel data regression model. The results of this study are: (1) there is a positive and significant effect between profitability on stock returns. (2) there is no positive and significant effect between profitability on stock returns.3. there is a positive effect of stock returns on the company's reputation The purpose of this study is to contribute to potential investors, this research is expected to increase the knowledge of investors on the company's financial information, especially in the property and real estate sectors.